2016
DOI: 10.1007/s11130-016-0590-1
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, a Compound from Natural Sources, a True Scientific Challenge – A Review

Abstract: Curcumin, a plant-derived polyphenolic compound, naturally present in turmeric (Curcuma longa), has been the subject of intensive investigations on account of its various activities. The implementation of safe, beneficial and highly functional compounds from natural sources in human nutrition/prevention/therapy requires some modifications in order to achieve their multi-functionality, improve their bioavailability and delivery strategies, with the main aim to enhance their effectiveness. The low aqueous solubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(129 citation statements)
references
References 63 publications
4
122
0
3
Order By: Relevance
“…A number of previous studies suggest that curcumin inhibits NF-κB expression and therefore additional downstream signaling pathways, ultimately leading to the silencing of inflammatory cytokines, including chemokine (C-X-C motif) ligand (CXCL)1 and CXCL2 (19); and to alterations in the expression of MMP-9, urokinase plasminogen activator (uPA), uPA receptor, intercellular adhesion molecule 1 and chemokine receptor 4 (3,72,75). In this manner, curcumin is likely to inhibit the growth and invasion of breast cancer, in part, by downregulating NF-κB signaling pathways.…”
Section: Targets Of Curcumin In Ras Signalingmentioning
confidence: 99%
“…A number of previous studies suggest that curcumin inhibits NF-κB expression and therefore additional downstream signaling pathways, ultimately leading to the silencing of inflammatory cytokines, including chemokine (C-X-C motif) ligand (CXCL)1 and CXCL2 (19); and to alterations in the expression of MMP-9, urokinase plasminogen activator (uPA), uPA receptor, intercellular adhesion molecule 1 and chemokine receptor 4 (3,72,75). In this manner, curcumin is likely to inhibit the growth and invasion of breast cancer, in part, by downregulating NF-κB signaling pathways.…”
Section: Targets Of Curcumin In Ras Signalingmentioning
confidence: 99%
“…In this study, we present our findings using two mitochondrial STAT3 inhibitors that are based on curcumin, a plant‐derived polyphenolic compound naturally present in turmeric ( Curcuma longa ) . Curcumin is a well‐known inhibitor of STAT3, and here, we have conjugated it to a mitochondrial‐targeting small molecule .…”
Section: Introductionmentioning
confidence: 99%
“…The tumours in the mice treated with MSN/CUR-PEI-FA were significantly smaller than those in the control mice and mice treated with free CUR (Figure 14(a,c,d)), with the latter two groups showing no difference in the tumour size. CUR has low bioavailability since it is rapidly metabolized or conjugated in vivo and is transformed into glucuronides and sulphates [43,44]. Our results demonstrated that MSN/CUR-PEI-FA could specifically target the tumour site, leading to the enhanced drug delivery and antitumour effects.…”
Section: In Vivo Antitumour Effectsmentioning
confidence: 79%